Numerical evaluation of two-loop QCD helicity amplitudes for gg → t t ¯ g $$ gg→ t\overline{t}g $$ at leading colour - Simon Badger; Matteo Becchetti; Colomba Brancaccio; Heribertus Bayu Hartanto; Simone Zoia (Journal of High Energy Physics)
Abstract We present the first benchmark evaluation of the two-loop finite remainders for the production of a top-quark pair in association with a jet at hadron colliders in the gluon channel. We work in the leading colour approximation, and perform the numerical evaluation in the physical phase space. To achieve this result, we develop a new method for expressing the master integrals in terms of a (over-complete) basis of special functions that enables the infrared and ultraviolet poles to be cancelled analytically despite the presence of elliptic Feynman integrals. The special function basis makes it manifest that the elliptic functions appear solely in the finite remainder, and can be evaluated numerically through generalised series expansions. The helicity amplitudes are constructed using four dimensional projectors combined with finite-field techniques to perform integration-by-parts reduction, mapping to special functions and Laurent expansion in the dimensional regularisation parameter.